Analisis Penerapan Metode Bag Weight Statistics Menggunakan SAP ECC 6 Dan Pengaruh Sistem Kalibrasi Berkala Di Weighbridge Dalam Upaya Mengurangi Terjadinya Over Weight Pada Semen Kantong - Muchtar, Akhyar; Fitriati, Andi (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2014)
One of the challenges faced by cement company is how to produce the final product in the form of cement as expected by the customer, both in terms of quality and quality, to maintain the trust of the costumer toward the product. The high of market demand lead to the need for the application of technology for the efficiency, in this case the application of bag weight statistics method to suppress or minimize the high case of overloaded or under loaded on the delivery ofcement packaging bags of 40 kg and 50 kg. The data in 2013, the total tonnage reaches over 128.831 tons per month. Potential of inefficiencies reaches 1.04 billion dollars. It does not include the distribution time wasted on re-checking. Bag Weight Statistics Method Using SAP ECC 6 inweighbridge is an effort to suppress the loss due to improper calibration system. This method observes the trend of weighbridge generated through monitoring SAP ECC 6 then take the lowest error values of the system as a reference. The lowest error values will then become a reference for the calibration of the system if any value exceeds the average of error valuesKeywords: Metode Bag Weigh Statistic, Weighbridge, SAP ECC 6, Kalibrasi